Investigation of quality of life scale and clinical severity of acne vulgaris patients who applied to dermatology outpatient clinic (Annals of Medical Research, 2023)
Aim: Acne Vulgaris is a skin disease characterized by acne and blackheads that appear on the face, chest, and back. This study, it was aimed to evaluate the life quality and determine the clinical severity of patients with acne vulgaris who applied to the dermatology outpatient clinic of our university.Materials and Methods: The study was conducted prospectively between January 01, 2022, and March 31, 2022. Seventy-one patients and 90 healthy volunteers who applied to the dermatology outpatient clinic were included. When the responses to the quality of life score were compared, the difference between the patient group and the control group was statistically significant.Results: Our study showed that acne vulgaris has negative effects on quality of life. In our study, we found that 40.8% of patients had a medium to high acne vulgaris score. When comparing the total responses to nine questions, the patient group had a score of 17.14 ± 6.53, while the control group had a score of 13.96 ± 5.22 (p
Keywords: Acne vulgaris; Psychology; Patients